Ascopolyporus tibetensis (Cordycipitaceae, Hypocreales): a new species from Tibet, China - Yu, Feng-Ming; Wei, De-Ping; Zhao, Qi; Tang, Song-Ming; Luangharn, Thatsanee (Phytotaxa, 2023)
The genus Ascopolyporus belongs Cordycipitaceae. Its members infect scale insects as necrotrophs, and produce stromata on the living stems of plants as biotrophs. In this study, we introduce a new taxon of Ascopolyporus that was collected from Tibet, China. Fresh stromata of the new taxon were located on the living stems of bamboo. The new taxon is described based on morphological characteristics and multigene phylogenetic analyses of ITS, LSU, and tef1 sequence data, and compared with closely related taxa. The new species Ascopolyporus tibetensis formed a distinct, well-supported lineage (100% MLBS, 1.00 BIPP) separated from A. galloide in the clade comprising A. griseoperitheciatus. Ascopolyporus tibetensis is diagnosed by the widest asci, globose to sub-globose stromata, yellow upper part and dark green lower part.